Personal Hurdles as Key Stimulants to Rural Entrepreneurship: Economic Implications for Owner-Managers - Agbenyegah, Albert Tchey; Dlamini , Bongani Innocent (Current Aspects in Business, Economics and Finance Vol. 6, 2022)
Entrepreneurship is known as one of the primary stimulants to economic development across the globe. Understanding personal hurdles could revive rural entrepreneurship to a growing venture. This study aims to investigate personal obstacles as disclosed by owner-managers in two rural settings in the Northern Cape Province (NCP). According to the literature, personal obstacles contribute to the increased failure of entrepreneurial activity. Personal obstacles were evaluated using the "Statistical Package for the Social Sciences" (SPSS). A survey method was employed to collect primary data, and descriptive analysis and frequency tables were used to examine all basic variables, including owner-managers' personal obstacles. Personal obstacles were determined using factor analysis. Formulated hypotheses for the study were tested through the applications of inferential statistics aided by the Analysis of Variance (ANOVA). Pearson Correlation techniques were used to determine relationships between dependent factors (rural entrepreneurial failures) and independent variables (resource, information, and infrastructural shortages). However, information and infrastructure have no substantial impact on REF. There was a moderately positive linear association found between the resource gap and REF. Furthermore, a low positive linear connection was found between REF and the two independent variables (information and infrastructural deficiencies). The findings point to the urgent need to source and train relevant resources in rural entrepreneurship ventures. Besides, resource gaps highly affect rural entrepreneurial failures (REFs) and drives economic downturn in rural areas. The study recommends the need to provide resources such building knowledge, information on rural entrepreneurship, and upskill human capabilities in rural entrepreneurship.